School or Work? The Role of Weather Shocks in Madagascar - Francesca Marchetta; David E. Sahn; Luca Tiberti (Institute of Labor Economics (IZA), 2018)
We examine the impact of rainfall variability and cyclones on schooling and work among a cohort of teens and young adults by estimating a bivariate probit model, using a panel survey conducted in 2004 and 2011 in Madagascar - a poor island nation that is frequently affected by extreme weather events. Our results show that negative rainfall deviations and cyclones reduce the current and lagged probability of attending school and encourage young men and, to a greater extent, women to enter the work force. Less wealthy households are most likely to experience this school-to-work transition in the face of rainfall shocks. The finding is consistent with poorer households having less savings and more limited access to credit and insurance, which reduces their ability to cope with negative weather shocks.
Keywords: Q54; J43; I25; 330; climate shocks; employment; schooling; Africa